1992
DOI: 10.1111/j.1365-3059.1992.tb02323.x
|View full text |Cite
|
Sign up to set email alerts
|

Axenic culture of Peridermium pini from single aeciospores

Abstract: For the first time with a rust fungus, continuously growing axenic cultures have been obtained from single spores. This was achieved with aeciospore sources of the pine stem rust Peridermium pini (Pers.) Lev. from Thetford Forest, East Anglia, but not with sources from north‐east Scotland. Approximately 30% of the single spores of two East Anglian sources out of the three tested developed into transferable and subculturable colonies on modified Harvey & Grasham's medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The two forms of the fungus, previously separated on the basis of their germ-tube morphology and cytology (GIBBS et al 1988) have now been shown to possess a high degree of cultural identity When the results here are taken together with the discovery that single aeciospores from some Thetford origins can produce colonies, while those of Morayshire origin cannot (PEI and GIBBS 1991), it is clear that major genetical differences exist between the two forms of I? pini in the UK.…”
Section: Discussionmentioning
confidence: 88%
“…The two forms of the fungus, previously separated on the basis of their germ-tube morphology and cytology (GIBBS et al 1988) have now been shown to possess a high degree of cultural identity When the results here are taken together with the discovery that single aeciospores from some Thetford origins can produce colonies, while those of Morayshire origin cannot (PEI and GIBBS 1991), it is clear that major genetical differences exist between the two forms of I? pini in the UK.…”
Section: Discussionmentioning
confidence: 88%
“…The stimulating effects of mass spores on mycelial growth have been observed in some rust fungi in attempts to establish axenic cultures from the spores. For example, P. graminis tritici (Bose & Shaw, 1971), Melampsora lini (Tuel, 1969) and Peridermium pini from Scotland (Pei & Gibbs, 1992) grew on artificial media only when mass spores were inoculated. Although the present results proved that each successful inoculation with a single spore resulted in the development of only one pustule, the high infection efficiency obtained in the experiment raises the question whether a single-spore infection can produce more than one pustule when more spores are applied.…”
Section: Discussionmentioning
confidence: 99%
“…(26) e Pucciniastrum sp. (27), Endocronartium harknessii (1), Peridermium pini (16), Cronartium flaccidum (13), Melampsora epitea (3), Melampsora larici-tremulae (14), Peridermium harknessii, Cronartium quercuum f. sp. banksinae e C. comandrae (24), Melampsoridium hiratsukanum (15).…”
mentioning
confidence: 99%